1998
DOI: 10.1021/om9707937
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diphospha-2-silaallylic Lithium Complexes and Anions:  Synthesis, Crystal Structures, Reactivity, and Bonding Properties

Abstract: Trichlorosilanes RSiCl3 (R = t-Bu, Mes, Cp*, Is, OAr) reacted with a 4-fold excess of lithium phosphanide ArPHLi (Ar = 2,4,6-tBu3C6H2) to form 1,3-diphospha-2-silaallylic complexes 3a−f. From the latter, the corresponding free allylic anions could be liberated by complexation of the lithium cation with [15]-crown-[5], as could be established on the basis of NMR spectra and X-ray structures. In addition, the bonding in the Li complexes was further investigated using ab initio calculations of double-ξ quality. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
2
26
0
1
Order By: Relevance
“…The low‐coordinate P and Si atoms in 2 are deshielded, resonating at low field: δ( 31 P)=128.7 and δ( 29 Si)=180 ppm ( 1 J Si=P =203.0 Hz, 1 J Si−P =141.3 Hz), respectively. Other described 2‐phosphanyl phosphasilenes 25 – 27 (Figure ) are significantly less stable and display similar spectroscopic features.…”
Section: Structure and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The low‐coordinate P and Si atoms in 2 are deshielded, resonating at low field: δ( 31 P)=128.7 and δ( 29 Si)=180 ppm ( 1 J Si=P =203.0 Hz, 1 J Si−P =141.3 Hz), respectively. Other described 2‐phosphanyl phosphasilenes 25 – 27 (Figure ) are significantly less stable and display similar spectroscopic features.…”
Section: Structure and Synthesismentioning
confidence: 99%
“…Stable 1,3‐diphospha‐2‐silaallyl lithiums 28 (Figure ) represent delocalized three‐center 3p π bonding systems with practically identical Si−P distances (e.g., 2.114(3) and 2.113(3) Å in 28 a ) and P‐Si‐P angles of 103–105° ( 28 a – c ). Geometric parameters of 28 a – c differ only slightly.…”
Section: Structure and Synthesismentioning
confidence: 99%
“…The Si-P distances in 4b,c (2.02 and 2.11 Å, respectively) are in a range for P-Si bond lengths that is significantly shorter than a P-Si single bond (2.25 Å). [3,5] In contrast to the σ-acceptor, π-donor substituents fluorine and phenyl, this P-Si bond length increases substantially to 2.31 and 2.35 Å, which is in the range for a single bond. Hydrogen-substituted 4a shows an intermediate situation, with an Si-P bond length of 2.22 Å.…”
Section: Resultsmentioning
confidence: 91%
“…Nevertheless, sterically protected Si=P double bonds have been generated and structurally characterized. [1][2][3][4][5] Similarly, phosphaallenes [6][7][8][9][10][11][12][13][14][15] as well as silaallenes, [16][17][18][19] trisilaallenes, [20][21][22] and even a 1-phospha-3-silaallene [23] have been synthesized and studied theoretically, [24][25][26][27][28][29][30] although the combination of both heteroatoms directly bonded to each other within a single allene system remains unknown so far. Earlier attempts to generate 1,3-diphospha-2-silaallenes by hydrogen chloride abstraction from suitable precursors with sterically hindered bases resulted either in Si-P bond cleavage or addition of the base to the Si-P unit.…”
Section: Introductionmentioning
confidence: 99%
“…1). Earlier study reported the structure of compounds where two Li-15C5 complex cations were linked by anionic [27] or neutral [28,29] bridges. However, these 2:2 complexes do not contain an uncoordinated CE.…”
Section: Resultsmentioning
confidence: 99%